Lobeglitazone inhibits LPS-induced NLRP3 inflammasome activation and inflammation in the liver - Seo, Hye-Young; Lee, So-Hee; Park, Ji Yeon; Han, Eugene; Han, Sol; Hwang, Jae Seok; Kim, Mi Kyung; Jang, Byoung Kuk (PLOS ONE, 2023)
Liver inflammation is a common feature of chronic liver disease and is often associated with increased exposure of the liver to lipopolysaccharide (LPS). Kupffer cells (KCs) are macrophages in the liver and produce various cytokines. Activation of KCs through the NLRP3 inflammasome pathway leads to release of proinflammatory cytokines and induces hepatocyte injury and hepatic stellate cell (HSC) activation. Lobeglitazone is a peroxisome proliferator-activated receptor gamma ligand and a type of thiazolidinedione that elicits anti-inflammatory effects. However, there is no clear evidence that it has direct anti-inflammatory effects in the liver. This study showed that lobeglitazone reduces LPS-induced NLPR3 inflammasome activation and production of proinflammatory cytokines in primary KCs and hepatocytes. Cytokines secreted by activated KCs increased hepatocyte inflammation and HSC activation, and lobeglitazone inhibited these responses. In addition, lobeglitazone suppressed liver fibrosis by inhibiting LPS-induced transforming growth factor (TGF)-β secretion and TGF-β-induced CTGF expression. The inhibitory effect of lobeglitazone on inflammasome activation was associated with suppression of liver fibrosis. These results suggest that lobeglitazone may be a treatment option for inflammation and fibrosis in the liver.